Influx of Rohingya Refugees in Bangladesh (Global Journal of Human-Social Science, 2021)
The Rohingya crisis has ascended as a potential threat to Bangladesh's inside steadiness. Strangely, Bangladesh is currently facilitating around a million displaced Rohingya people which outcomes in genuine worry of national security. Although the repatriation of Rohingya to their homeland will be ambiguous in coming days and at the same time, their stay in Bangladesh might be continuing for a longer period of time. Bangladesh government is struggling as well to control and manage migration risks undermining public confidence in the integrity of government policy. Bangladesh government has been making diplomatic efforts in persuading Myanmar to repatriate the refugees over months but in reality, it is highly unlikely the Bangladesh government will succeed in sending the refugees back to Myanmar in any shortest possible time. Apart from keeping diplomatic efforts continue for their repatriation to Myanmar, Bangladesh government should have appropriate security strategy for addressing the concern of security until arriving in an amicable solution of this prolonged crisis. The paper attempts to discover the potential threat of Rohingya refugees towards the national security as well as to understand the progress Bangladesh has made so far for their repatriation to Myanmar.
Keywords: rohingya; stateless community; livelihood; national security and repatriation